2021
DOI: 10.3390/brainsci11091252
|View full text |Cite
|
Sign up to set email alerts
|

SUNCT/SUNA in Pediatric Age: A Review of Pathophysiology and Therapeutic Options

Abstract: The International Classification of Headache Disorders, 3rd edition (ICHD3) defines Short-lasting Unilateral Neuralgiform Headache Attacks (SUNHA) as attacks of moderate or severe, strictly unilateral head pain lasting from seconds to minutes, occurring at least once a day and usually associated with prominent lacrimation and redness of the ipsilateral eye. Two subtypes of SUNHA are identified: Short-lasting Unilateral Neuralgiform headache attacks with Conjunctival injection and Tearing (SUNCT) and Short-last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…SUNCT is generally medically refractory, which compels the search for alternative treatment paradigms. 5 Though direct PPG block with lidocaine has been reported to acutely resolve symptoms in a patient with SUNCT, 12 a systematic review on the use of PPG blockade for headache syndromes did not demonstrate a cure for the two SUNCT cases that were included. 13 Pulsed radiofrequency of the PPG has been explored as a possible treatment for SUNCT, and this resulted in symptom resolution in seven out of nine cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SUNCT is generally medically refractory, which compels the search for alternative treatment paradigms. 5 Though direct PPG block with lidocaine has been reported to acutely resolve symptoms in a patient with SUNCT, 12 a systematic review on the use of PPG blockade for headache syndromes did not demonstrate a cure for the two SUNCT cases that were included. 13 Pulsed radiofrequency of the PPG has been explored as a possible treatment for SUNCT, and this resulted in symptom resolution in seven out of nine cases.…”
Section: Discussionmentioning
confidence: 99%
“…1 The most widely accepted theory is that an abnormality in the posterior hypothalamus precipitates activation of the trigeminalautonomic reflex. [4][5][6] Functional imaging and brain stimulation studies have identified activation of the posterior hypothalamic gray matter in TACs, which in turn leads to heightened sensitivity to noxious stimuli via the pain-modulating system of the trigemino-hypothalamic tract and the trigeminovascular system. [4][5][6] These systems then stimulate internal trigger areas in the hypothalamus and trigeminal nucleus caudalis, which activate the superior salivatory nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For PH the largest number of reported cases in a single study with a documented tobacco exposure history was 74 patients (lacked sex distribution), SUNCT and SUNA 20 patients and for HC a study of 34 patients (no sex distribution was noted) (14)(15)(16). All pediatric and adolescent investigations had no personal or secondary cigarette smoke exposure data (17)(18)(19). None of the original case descriptions for each of these unique conditions mentioned a smoking history (20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Cesaroni et al, in their review, analyzed the literature evidence about the key features of therapeutic options, during the developmental age, of Short-lasting Unilateral Neuralgiform headache attacks with Conjunctival injection and Tearing (SUNCT) and Short-lasting Unilateral Neuralgiform headache attacks with cranial Autonomic symptoms (SUNA), rare primary headache syndromes belonging to the group of Trigeminal Autonomic Cephalalgias. Thanks to a review of 60 articles, the authors described the pathophysiology of SUNCT and SUNA and analyzed the therapeutic options available to date, especially underlining less-invasive and risk-free therapies as possible treatment options for pediatric patients [6].…”
mentioning
confidence: 99%